Artificial intelligence in the context of digital marketing communication - Bormane, Santa; Blaus, Egita (Frontiers in Communication, 2024)
The development of digital transformation both in the European Union and in Latvia is affected by a variety of regulations, laws, guidelines and programmes, the objectives of which determine the use of contemporary digital technologies (including artificial intelligence) and the development of digital skills for enhancing the operational efficiency and productivity of businesses. The goal of the article is to identify the disadvantages and risks associated with the use of AI in digital marketing communication. To complete the goal the use of AI was brought up to date, covering both concepts and applications, as well as advantages of using AI in digital marketing communication, because the advantages are the causes of any disadvantages and potential risks. In order to attain the goal, bibliometric analysis, monographic method and secondary data analysis was used, as well as scientific literature was analysed. As a result, the following types of artificial intelligence were identified: machine learning, computer vision, robotics, speech recognition and natural language processing, as well as related technologiescloud computing technologies and augmented and virtual reality. The possibilities of using artificial intelligence and integrating it into various digital marketing communication activitiessearch engine marketing, digital advertising, e-mail marketing, social media marketing, public relations, sales promotion, personal selling, as well as review marketing and in neuromarketingwere explored. The use of artificial intelligence presents many advantagesfinancial savings, easier processing and analysis of high data volumes, time savings, applicability in different spheres, non-stop operation (immediate response), and personalised marketing strategies. However, a number of disadvantages were found, too, as there are potential risks associated with feasibility studies, technology compliance, privacy and data protection, cybersecurity, psychological information manipulation attacks, competence, structural labour availability, automation and technology, and outsourced service providers or third parties.